INDONESIAN LANDSCAPE PAINTING BASED ON ARTIFICIAL INTELLIGENCE (AI) VIEWPOINTS - Fahriza, Ba’im; Mujiyono (Eduarts: Jurnal Pendidikan Seni, 2025)
A landscape is a visual representation of an area that encompasses both natural and man-made elements. In the context of fine art, particularly painting, a landscape not only displays natural beauty but also implies aesthetic, cultural, and emotional values. The development of digital technology such as artificial intelligence has opened up new opportunities in the creation of paintings. This study project aims to produce an Indonesian landscape painting that presents visual freshness through an AI perspective. The methods used in the creation process include three main approaches: experiential AI, local aesthetics, and a naturalistic approach. The creation process is divided into three stages: pre-creation, creation, and post-creation. The resulting work is entitled "Encoded Gaze." The work depicts a rural Indonesian landscape. Cultural and natural elements are combined with digital surveillance symbols in the form of CCTV cameras. Formally, this work combines elements of line, color, and texture, as well as ideas that produce a composition within the context of local culture. This study project produces a beautiful painting through the integration of AI and modern art aesthetics. The painting, besides being beautiful, is also aesthetically meaningful in context. This beauty maintains the prompts designed through a reflective and valuable aesthetic process.